2013
DOI: 10.2527/jas.2012-5656
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of genetic parameters and quantitative trait loci for growth traits in Fraser strain Arctic charr (Salvelinus alpinus) reared in freshwater and brackish water environments

Abstract: To determine the potential for genetic improvement in Fraser strain Arctic charr (AC, Salvelinus alpinus), we calculated genetic parameters for BW and condition factor (K) and tested if previously identified QTL for these traits were detectable across a commercial broodstock reared in both freshwater (FRW) and brackish water (BRW). Individuals from 30 full-sib families were reared up to 29 mo of age in FRW and BRW tanks at a commercial facility. Heritability for BW and K was moderate in FRW (0.29 to 0.38) but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…On the contrary, a low genetic correlation ( r g = 0.45 ± 0.09) between freshwater and salt water environments has been reported in Nile tilapia by Luan et al (2008). A similar finding was also reported by Mas-Muñoz et al (2013) for harvest weight ( r g = 0.56) and specific growth rate ( r g = 0.27) between intensive recirculation aquaculture system (RAS) and semi-natural environment (POND) in common sole ( Solea solea ), Arctic charr ( Salvelinus alpinus ) by Chiasson et al (2013) and rainbow trout (Sae-Lim et al, 2013). These authors suggested that there was a strong genotype by environment interaction between these diverse environments used in their studies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the contrary, a low genetic correlation ( r g = 0.45 ± 0.09) between freshwater and salt water environments has been reported in Nile tilapia by Luan et al (2008). A similar finding was also reported by Mas-Muñoz et al (2013) for harvest weight ( r g = 0.56) and specific growth rate ( r g = 0.27) between intensive recirculation aquaculture system (RAS) and semi-natural environment (POND) in common sole ( Solea solea ), Arctic charr ( Salvelinus alpinus ) by Chiasson et al (2013) and rainbow trout (Sae-Lim et al, 2013). These authors suggested that there was a strong genotype by environment interaction between these diverse environments used in their studies.…”
Section: Discussionsupporting
confidence: 85%
“…Square root transformation used in this study reduced the magnitude of the difference in the heritability estimates for body weight between the two environments. The slight difference in heritability between grow-out testing environments was also reported in Nile tilapia or other fish species, such as Artic char (Chiasson et al, 2013) and rainbow trout (Sae-Lim et al, 2013). However, a meta-analysis of 26 studies in various aquaculture species indicated that the effect size of the difference in heritability for body weight between contrasting environments was not significant, P > 0.05 (Nguyen, unpublished results).…”
Section: Discussionmentioning
confidence: 54%
“…Hence, the lack of similar effects of parental alleles on body length in the wild and the hatchery further supports the importance of environment influencing the genetic architecture of complex traits, such as growth. This is consistent with recent QTL mapping work on growthrelated traits in Salvelinus alpinus (Arctic charr) that reported a number of environment-specific QTLs when fish were reared in freshwater and brackish water environments (Chiasson et al 2013).…”
Section: Allele Lengthsupporting
confidence: 91%
“…This is consistent with recent QTL mapping work on growth‐related traits in Salvelinus alpinus (Arctic charr) that reported a number of environment‐specific QTLs when fish were reared in freshwater and brackish water environments (Chiasson et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, 10 linkage groups contain significant body weight QTL in rainbow trout, Oncorhynchus mykiss, from multiple strains (Wringe et al 2010). Other studies have shown that QTL can vary between strains and across rearing environments Magee 2011;Chiasson et al 2013). The identity of the genes responsible for the QTL effects has been inferred though known colocalization of a particular candidate gene within the QTL region or inferred co-localization through in silico comparative synteny analyses with model species (Haidle et al 2008;Moghadam et al 2007;Viñas et al 2012).…”
Section: Introductionmentioning
confidence: 99%